1996
DOI: 10.1007/bf03189717
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofTamarindus indica L. on the bioavailability of aspirin in healthy human volunteers

Abstract: The influence of Tamarindus indica L. fruit extract incorporated in a traditional meal on the bioavailability of aspirin tablets 600 mg dose was studied in 6 healthy volunteers. There was a statistically significant increase in the plasma levels of aspirin and salicylic acid, respectively, when the meal containing Tamarindus indica fruit extract was administered with the aspirin tablets than when taken under fasting state or with the meal without the fruit extract. The Cmax, AUC0-6h and t1/2 for aspirin increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…A clinical study [34] performed on six healthy volunteers showed that a tamarind extract incorporated in a traditional meal increased plasma levels of aspirin and salicylic acid (a metabolite of aspirin). The mechanism of such interaction is not known.…”
Section: Aspirinmentioning
confidence: 99%
“…A clinical study [34] performed on six healthy volunteers showed that a tamarind extract incorporated in a traditional meal increased plasma levels of aspirin and salicylic acid (a metabolite of aspirin). The mechanism of such interaction is not known.…”
Section: Aspirinmentioning
confidence: 99%
“…The organic acids and pectin are believed to contribute at least to its laxative effect. With regards to herb–drug interactions, tamarind has been reported to increase the bioavailability of aspirin, leading to gastrointestinal bleeding (16). Whether or not tamarind interacts with other NSAIDs in a similar manner has not yet been documented.…”
Section: Interactions With Tamarind (Tamarindus Indica)mentioning
confidence: 99%
“…There are several reports of other commonly consumed supplements with significant effects on drug bioavailability and disposition. For example, kola nut has been reported to cause a significant decrease in the plasma concentration of halofantrine and its metabolite when co‐administered and Tamarindus indica the major component of a local drink widely taken in the Northern part of Nigeria has been reported to significantly decrease the bioavailability of aspirin in healthy human subjects …”
Section: Discussionmentioning
confidence: 99%